La pollution : le point de vue d’un réassureur - Raymond, Michel J. (Assurances, 1988)
This paper is an attempt to present the problems which result for the insurance and reinsurance industry from pollution. It can only provide an insight into the situation as it now stands. Technological developments in nearly all fields are unusually rapid and facts and processes which are still thought today to be fully up-to-date may be outdated by tomorrow. This paper is intended to provide an incentive to follow up the problem both in its general and in its individual aspects in order to establish as reasonable as possible a position for the insurance industry, from a Reinsurer's point of view.